2002
DOI: 10.1530/eje.0.1470103
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that luteinising hormone receptor polymorphisms may contribute to male undermasculinisation

Abstract: Background: The luteinising hormone receptor (LHR) is necessary for the stimulation of androgen production and male genital development. It contains three protein polymorphisms: a leucine and glutamine insertion between codons 8 and 9 (LQ+) and two amino acid substitutions (N291S, N312S). Objectives: To determine whether these LHR polymorphisms are associated with male genital undermasculinisation or the androgen receptor polyglutamine repeat polymorphism (AR(Q)n ), which contributes in some cases to the cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As this allele is absent in most TC cases, the clinical relevance of this finding is limited, but may be interesting from a biological point of view. The polymorphic 291Ser allele has been shown to increase the LHR activity (Piersma et al, 2007) whereas another study found that the frequency of the wild type 291Asn allele was significantly higher in the undermasculinized group than in the controls (Mongan et al, 2002). Thus, there is a possibility of an altered testicular testosterone production dependent on an individual's LHR genotype.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As this allele is absent in most TC cases, the clinical relevance of this finding is limited, but may be interesting from a biological point of view. The polymorphic 291Ser allele has been shown to increase the LHR activity (Piersma et al, 2007) whereas another study found that the frequency of the wild type 291Asn allele was significantly higher in the undermasculinized group than in the controls (Mongan et al, 2002). Thus, there is a possibility of an altered testicular testosterone production dependent on an individual's LHR genotype.…”
Section: Discussionmentioning
confidence: 98%
“…The polymorphic 291Ser allele has been shown to increase the LHR activity (Piersma et al. , 2007) whereas another study found that the frequency of the wild type 291Asn allele was significantly higher in the undermasculinized group than in the controls (Mongan et al. , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The rs2293275 is located in exon 10 near a glycosylation site, which has been hypothesized to reduce the receptor activity (14,27,29). Although associations between the LHCGR polymorphism and impaired spermatogenesis and under-masculinization have been detected (14,27,30), it has also been shown that deletion of exon 10 only affects the sensitivity to LH and not hCG, which could be an explanation for the lack of an association (31). For two of the LHCGR polymorphisms, none were homozygous carriers of the minor allele, and in the FSH-related genotype groups, some of the minor allele groups were small.…”
Section: Discussionmentioning
confidence: 99%
“…The human LH-hCG cluster consists of one LHβ and 6 hCGβ genes and pseudogenes. 80 LH-receptor polymorphisms have also been described (such as Asn291Ser and Asn312Ser) in association with undermasculinization 81 and Leydig cell hypoplasia. 71 In particular, four O-linked glycosylation linkages present in an extended C-terminal portion of hCGβ (but not LHβ) increase intact hCG half-life to 24 to 30 hours compared with 1 hour for LH, and augment biopotency by limiting hCG-receptor dissociation.…”
Section: Gonadotropins and Cognate Receptorsmentioning
confidence: 99%